Splenic artery aneurysms - a systematic review of the literature - Machado,Marta (2024)
Abstract Introduction: Splenic artery aneurysms (SAA) are the most frequent (50 to 75%) abdominal visceral arterial aneurysms. In autopsy studies, the overall incidence is 0.01%, increasing to 10.4% with age. Due to their rarity, there is a lack of data, so we aimed to perform a systematic review of available SAA data.. Methods: A systematic review was performed according to the PRISMA guidelines. A literature search was performed using the Medline database from January 2019 to January 2024. Only full-text articles were considered, including patients with true SAA treated by endovascular (ET) and/or open surgical (OS) means. Only articles published in English or Portuguese were considered. The investigated outcomes were postoperative complications, reinterventions, and mortality. Results: Of the 289 articles identified during the initial literature search, 87 were included in qualitative synthesis. One thousand sixty-one patients were identified with 1085 reported SAAs. The mean age was 51.62 years +/- 14.57, with older patients in the OS group (OS 54.49 years +/-15.95 vs. ET 51.92 years +/-12.83) and 39.8% (range 29.5-50.0) were male (OS 34.5% [16.2-52.8] / ET 41.7% [27.0-56.3]). A total of 12.6% (0.3-24.9%) were detected during pregnancy, with a higher frequency of pregnancy also in the OS group (OS 29.5% [0.0-9.3])/ ET 7.2% [0-14.6%]) The mean diameter was 3.18cm +/- 2.07 (OS 4.95cm +/- 3.74 vs. ET 3.10cm +/- 1.92). The frequency of rupture was 2.8% (0.0-8.9%) and much higher in the OS group (OS 37.5% [0-100%] vs. ET 6.5% [0.0-23.4]) The types of intervention reported were ET (744 patients) and OS (317 patients: 281 conventional open reconstruction, 25 laparoscopic, and 11 robotic). Postoperative complication rates were 12.4% (2.1-22.6) in the ET group and 9.1% (5.6-12.6) in the OS. The reintervention rate at 30 days was 5.2% (1.6-10.4) in the ET group. Reintervention after OS was 4.7% (2.2-7.2). Overall, there were three perioperative deaths, all in the OS group (mortality: 23.0 [95% CI 0.0-96.3]. Conclusion: SAAs rupture is associated with high mortality, so timely diagnosis and management are essential to attain a satisfactory outcome. A detailed and individualized analysis of each case and a sufficient understanding of the anatomy and hemodynamics of a particular aneurysm should guide the therapeutic decision. OS has good results in treating SAA with lower morbidity and reintervention than ET. However, ET should be a viable alternative in high-risk patients with favorable anatomy.